(untitled) (Italian Journal of Public Health, 2007)
Aim: Risk charts and risk score, based on the global absolute risk, are key tools for CVD risk assessment. When applied to the population from which they derive, they provide the best estimate of CVD risk. That is why the CUORE Project has among its objectives the assessment of the Italian population’s cardiovascular risk, identifying the model for the prediction of coronary and cerebrovascular events in 10 years. Methods: Data fromdifferent cohorts enrolled in the North, Centre and South of Italy between the 1980s and the 1990s were used. From the 7,056 men and 12,574 women aged 35-69 years, free of cardiovascular disease at base-line and followed up for a mean time of 10 years for total and cause-specific mortality and non fatal cerebrovascular and coronary events, 894 major cardiovascular events (596 coronary and 298 cerebrovascular) were identified and validated. To assess 10-year cardiovascular risk, the risk score and risk chart were developed for men and women separately, considering the first major coronary or cerebrovascular event as the endpoint. Results: The risk score is applied tomen andwomen aged 35-69 years and includes age, systolic blood pressure, total cholesterol, HDL-cholesterol, smoking habit, diabetes and hypertension treatment using continuous values when possible. The risk chart is applied to persons aged 40-69 years and includes the same risk factors as risk score, except for HDL-cholesterol and hypertension treatment, and uses categorical values for all variables. Conclusions: The risk score and risk chart are easy-to-use tools which enable general practitioners and specialists to achieve an objective evaluation of the absolute global cardiovascular risk of middle-aged persons in primary prevention.